Cementless Porous‐Coated Metaphyseal Sleeves Used for Bone Defects in Revision Total Knee Arthroplasty: Short‐ to Mid‐Term Outcomes. Issue 2 (7th December 2022) - Shen, Junmin; Zhang, Ti; Zhang, Yanchao; Dong, Yu; Zhou, Yonggang; Guo, Lingfei
Abstract : Objectives: While many studies have presented excellent short‐term outcomes of the metaphyseal sleeves used in revision total knee arthroplasty (TKA), currently published mid‐term results remain limited and some controversial issues remain unresolved. The purpose of this study was to investigate clinical and radiographic mid‐term outcomes of the sleeves for the management of metaphyseal bone defects in revision TKAs. Methods: From 2015 to 2019, 44 patients (45 knees) who were operated with cementless porous‐coated metaphyseal sleeve in revision TKA were included in this study. Bone defects were assessed according to Anderson Orthopaedic Research Institute Classification. On the tibial side, there were 37 type II and six type III, and with regards to the femur, 15 were type II, and four were type III. Through reviewing electronic records, data were collected, including baseline demographics, operative details, information of prothesis, and complications. Clinical and radiographic evaluations were performed, including Knee Society Scores (KSS), Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), range of motion (ROM), the radiolucent line, level of joint line, and implant survival rate. Statistical analysis was performed by paired t ‐test for clinical and radiographic indexes. Results: The mean follow‐up time was 4.4 ± 1.4 years. During surgery, sleeve‐related fractures were encountered in four (8.9%) knees, including incomplete tibial fracture of lateral cortex in one knee and of medial cortex in two knees, and longitudinal femoral metaphyseal fracture in one knee. Unions were achieved in all cases at the final follow‐up. Significant improvements in KSS and WOMAC scores were found at the final follow‐up, respectively, from 83.8 ± 29.1 to 152.9 ± 31.0 ( t = −12.146, p < 0.001) and from 148.4 ± 42.3 to 88.1 ± 52.5 ( t = 6.025, p < 0.001). The mean ROM improved from 88.7 ± 31.9° to 113.7 ± 13.7° ( t = −5.370, p < 0.001). A 75 mm length of cementless stem was used in all patients and only one patient was identified as tibial end‐of‐stem pain. No sleeve‐related revision occurred, and one patient was diagnosed with early postoperative infection and was treated with irrigation and debridement, polyethylene liner exchange, and appropriate antibiotic treatment. The overall implant survival was 97.8% with the endpoint reoperation and 100% with the endpoint revision. Osseointegration at the bone‐sleeve interface was found in all patients and no loosening happened. Satisfactory alignment between 3° varus and 3° valgus was achieved in all but not in three patients. Conclusion: The use of metaphyseal sleeves in the treatment of bone defects in rTKAs can provide stable fixation and significantly improve the clinical scores at the midterm follow‐up. In addition, the rare occurrence of end‐of‐stem pain suggests routine use of cementless stems. Although there are chances of intraoperative fractures, it has no negative effect on outcome when managed properly. Abstract : The use of metaphyseal sleeve combined with cementless stem and condylar restricted prosthesis with an MBT rotating platform in the treatment of severe bone defect showed satisfactory outcome.